2017
DOI: 10.1016/j.bjps.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two cadaveric acellular dermal matrices for immediate breast reconstruction: A prospective randomized trial

Abstract: AlloDerm RTU and AlloMaxTM are two acellular dermal matrices (ADMs) used in implant-based breast reconstruction. In this study, we examined whether different processing methods for the ADMs lead to a disparity in histologic, clinical, and financial outcomes after breast reconstruction. Thirty patients undergoing implant-based breast reconstruction were randomized into AlloMax or AlloDerm arms (n = 15, each). ADM was placed at the time of immediate reconstruction. Patients were evaluated for complications on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Although abundant data support the use of ADMs, 3137 several recent meta-analyses confirm the need for additional level 1 and 2 evidence to establish how one ADM compares to another and how they are influenced by patient and therapeutic factors. There are a limited number of randomized control trials specifically comparing one ADM to another when providing support for submuscular reconstructions, 13,14,16 and none, in the context of prepectoral reconstructions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although abundant data support the use of ADMs, 3137 several recent meta-analyses confirm the need for additional level 1 and 2 evidence to establish how one ADM compares to another and how they are influenced by patient and therapeutic factors. There are a limited number of randomized control trials specifically comparing one ADM to another when providing support for submuscular reconstructions, 13,14,16 and none, in the context of prepectoral reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…This study, however, may have been underpowered as complications rates of 8% versus 26.1% were not found to be significantly different. 16 To our knowledge, there are no published RCTs comparing ADMs to one another when used in prepectoral breast reconstruction, an increasingly popular technique for prosthetic reconstruction Given the lack of high-quality studies available, a significant need remains for carefully designed and adequately powered RCTs comparing outcomes between various ADMs in submuscular and prepectoral prosthetic breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Low quality evidence from three small trials comparing different types of mesh suggests no difference in outcomes 121314. Of these, one very low quality underpowered study14 reported a higher rate of implant loss and more postoperative pain, fatigue, and impact on family life with biological mesh compared with synthetic mesh.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…An updated literature review has identified two small single centre randomised controlled trials comparing complications of different human acellular dermal matrixes1213 and shows no substantial differences in outcomes between different products (table 1). These studies were not reported in sufficient detail for the risk of bias to be formally assessed, but as the trials were largely explanatory, the results are unlikely to be generalisable.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…Immediate breast reconstruction (IBR) received an important boost in popularity as a consequence of the advent of ADMs [ 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The use of ADMs showed encouraging results but conflicting reports as well [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. ADMs-assisted breast reconstruction can be divided into pre-pectoral and submuscular.…”
Section: Introductionmentioning
confidence: 99%